THE EXPERIENCE OF PNEUMOCOCCAL CONJUGATE VACCINE USAGE IN ORPHANAGE INSTITUTION OF THE REPUBLIC OF MORDOVIA - A. A. Brovkina; L. A. Balykova; N. B. Kulagina (Вопросы современной педиатрии, 2012)
The experience of pneumococcal vaccine usage in the inmates of the Orphanage for Children with Organic Central Nervous System with Psychic Disturbances is discussed in this article. Taking into account the high rate and severe course of acute pneumonia among such children, 120 dosages of pneumococcal polysaccharide conjugate adsorbed vaccine were used in order to inoculate 48 children. Local and general mild reactions were registered in 8,3% of all the cases. It was established, that development of respiratory diseases in vaccinated children were 5,4 times rarer than in non-vaccinated ones. It was shown, that 1 year after the vaccination the infectious morbidity was 6 and 1,7 times lower among vaccinated and non-vaccinated children, respectively.